PENGHAMBATAN PERTUMBUHAN BAKTERI PADA BOKAR DENGAN ASAP CAIR SERBUK KAYU - Yulita, Eli (Balai Riset dan Standardisasi Industri Palembang, 2010)
The influences of liquid smoke from pyrolisis of sawdust of rubber wood (Hevea brasiliensis M) and gelam wood (Melaleuca leucadendron L) on qualities of processed rubber material were studied. The experiment was designed using factorial completely randomized design with two factors for crumb rubber study, i.e liquid smoke from sawdust of rubber wood (Hevea brasiliensis M) (0%, 5%, 10% and 15%). And gelam wood (Melaleuca leucadendron L) (0%, 5%, 10% and 15%). Observed parameters were diameter of inhibition zones and total plate count. The addition of liquid smoke into crumb rubber could inhibit the bacterial growth, showed by clear zone of 2000 mm in diameter produced around the liquid smoke spot (treatmen K10G15) and total plate count of 2,92 log CFU/ml (treatmen K10G15).